1990
DOI: 10.1136/pgmj.66.771.16
|View full text |Cite
|
Sign up to set email alerts
|

Hyperostosis frontalis interna, acromegaly and hyperprolactinaemia

Abstract: Summary:The association between hyperostosis frontalis interna (HFI), acromegaly and hyperprolactinaemia was investigated. Thirty six acromegalic patients, of whom 19 had hyperprolactinaemia, were compared with 36 randomly-selected, age-sex matched controls. There was a higher prevalence of HFI in the skull X-rays of the acromegalic cohort (P = 0.0002) when compared to the control group. This difference was apparent in both men (P = 0.01) and women (P = 0.01). Acromegalic patients with hyperprolactinaemia also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…This was the case up to the 50–59 year old age group. Following that, HFI rates appear to remain relatively consistent, as is similarly reported in other research (Fulton, Shand, Ritchie, & McGhee, ; Herschkovitz et al, ; May, Peled, Dar, Cohen, et al, 2011; Nikolić et al, ; Win & Aparici, ). The results of this study, therefore, support the findings of an age‐related increase in HFI reported in the general literature but also confirm a plateau in post‐menopausal age‐related manifestation of HFI in the 50+ year age groups.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This was the case up to the 50–59 year old age group. Following that, HFI rates appear to remain relatively consistent, as is similarly reported in other research (Fulton, Shand, Ritchie, & McGhee, ; Herschkovitz et al, ; May, Peled, Dar, Cohen, et al, 2011; Nikolić et al, ; Win & Aparici, ). The results of this study, therefore, support the findings of an age‐related increase in HFI reported in the general literature but also confirm a plateau in post‐menopausal age‐related manifestation of HFI in the 50+ year age groups.…”
Section: Discussionsupporting
confidence: 83%
“…Increases of 72% free testosterone, 17% testosterone 16% androstenedione were all reported in obese females as well as increases of 47% estradiol, 89% free estradiol and 47% estrone (Key et al, ). HFI has also been associated with significant increases of androgen levels, including free testosterone (Fulton et al, ) as well as serum DHEA, DHEA‐S and total testosterone in past studies of pre‐menopausal females without signs of virilism (Kollin & Fehér, ). Androgenicity is highly dependent on FT and the associated lower levels of SHGB (Abdel‐Rahman & Hurd, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual hormones for example, oestrogen stimulation,1–could play a part in the emergence of HFI and explain its predominance among female. Other metabolic disorders or endocrinopathies have been highlighted, such as acromegaly (especially when associated with hyperprolactinemia),10 11 diabetes or leptin hyper secretion 8 12. Genetic predisposing factors are also involved 6 13…”
Section: Discussionmentioning
confidence: 99%
“…Pawlikowski and Komorowski (1987) stated that 43.2% of women with hyperprolactinemia-induced galactorrhea had concurrent HFI. Fulton et al (1990) correlated acromegaly with increased occurrence of HFI and hyperprolactinemia. Mulhern et al (2006) suggest that genetic factors and environmental factors such as dietary phytoestrogens may explain the high incidence of HFI in the Anasazi at Pueblo Bonito.…”
Section: Discussionmentioning
confidence: 95%